Characterization of multi-scale porous structure of fly ash/phosphate geopolymer hollow sphere structures: From submillimeter to nano-scale. (January 2015) - Li, Ruifeng; Wu, Gaohui; Jiang, Longtao; Sun, Dongli
Graphical abstract: Highlights: Porous structure of HSS was characterized from sub-millimeter to nano-scale. Hollow fly ashes and sub-millimeter irregular open cells were found by CT and CSLM. Micro-sized open cell in gaps between fly ashes showed normal/bimodal distribution. PG was mainly composed of amorphous Al–O–P nano-pore area and α-Al2 O3 . Nano-pores (mainly from 10 to 100 nm) demonstrated a quasi-normal distribution. Abstract: In the present work, the porous structure of fly ash/phosphate geopolymer hollow sphere structures (FPGHSS), prepared by pre-bonding and curing technology, has been characterized by multi-resolution methods from sub-millimeter to nano-scale. Micro-CT and confocal microscopy could provide the macroscopic distribution of porous structure on sub-millimeter scale, and hollow fly ashes with sphere shape and several sub-millimeter open cells with irregular shape were identified. SEM is more suitable to illustrate the distribution of micro-sized open and closed cells, and it was found that the open cells of FPGHSS were mainly formed in the interstitial porosity between fly ashes. Mercury porosimeter measurement showed that the micro-sized open cell of FPGHSS demonstrated a normal/bimodal distribution, and the peaks of pore size distribution were mainly around 100 and 10 μm. TEM observation revealed that the phosphate geopolymer was mainly composed of the porous area with nano-pores and dense areas, which were amorphous Al–O–P phase and α-Al2 O3 respectively. The pore size of nano-pores demonstrated a quasi-normal distribution from about 10 to 100 nm. Therefore, detailed information of the porous structure of FPGHSS could be revealed using multiple methods.